2020
DOI: 10.1002/pds.4964
|View full text |Cite
|
Sign up to set email alerts
|

Age and postoperative opioid prescriptions: a population‐based cohort study of opioid‐naïve adults

Abstract: Purpose: Opioids are commonly prescribed for acute pain after surgery. However, it is unclear whether these prescriptions are usually modified to account for patient age and, in particular, opioid-related risks among older adults. We therefore sought to describe postoperative opioid prescriptions filled by opioid-naïve adults undergoing four common surgical procedures.Methods: This retrospective cohort study used individually linked surgery and prescription opioid dispensing data from Ontario, Canada to create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In Canada, age has been associated with a decreased proportion of patients that filled a postoperative opioid prescription. However, the initial prescription did not typically differ in older adults 22 . In our analysis, it was difficult to isolate the effect of the age.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In Canada, age has been associated with a decreased proportion of patients that filled a postoperative opioid prescription. However, the initial prescription did not typically differ in older adults 22 . In our analysis, it was difficult to isolate the effect of the age.…”
Section: Discussionmentioning
confidence: 78%
“…However, the initial prescription did not typically differ in older adults. 22 In our analysis, it was difficult to isolate the effect of the age. However, the largest study, with 69 456 patients, and with a high quality of evidence, showed a high rate of persistent use of opioids after hip fracture surgery: more than 15% in opioid-naı ¨ve patients, and more than 60% in preoperative opioid users.…”
Section: Discussionmentioning
confidence: 98%
“…2 While our study does not examine opioid misuse and abuse outcomes, prior work has shown strong associations between the number and duration of opioid prescription refills and postoperative opioid misuse among formerly opioid naive surgical patients, 3 as well as potential for diversion and misuse of unused opioids. 29 Coupled with the marked variability in opioid prescribing practices across countries, 27 this suggests that overall provider postoperative opioid prescribing practices may still be an important target for interventions aimed at deterring inappropriate prescribing and reducing opioid related harms. 30,31 The actual spread in opioid prescribing by surgeons in the highest and lowest quartiles of practice was relatively small, which may explain the overall null result in our primary analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We accounted for specific patient characteristics that, based on both biologic plausibility and previous literature, may be associated with filling an analgesic prescription postoperatively, including age, sex, income quintile, preoperative opioid use, and Charlson comorbidity score. [29][30][31] Finally, we adjusted for surgery type, because the volume of each surgical procedure changed over time, and each surgical procedure may be associated with varying degrees of pain and postoperative analgesic requirements.…”
Section: Discussionmentioning
confidence: 99%